Preferensi Masyarakat Terhadap Penggunaan Telemedicine Sebagai Pendukung Sarana Kesehatan pada Masa Pandemi Covid-19 di DKI Jakarta - Tasya Rahma Araminta; Mada Sophianingrum (Jurusan Perencanaan Wilayah dan Kota, 2023)
The Covid-19 pandemic has become a great challenge for cities around the world, one of which is DKI Jakarta, to adapt to the impact it has. One of the biggest impacts of the pandemic is health services that become vulnerable to experiencing over capacity during the pandemic. This condition gave rise to a new phenomenon, namely the use of telemedicine as a form of community adaptation to overcome the problem of limited access to health services when a wave of COVID-19 cases occurred. As a form of public service, it is important to know the preferences of the community as users of telemedicine, so that later the benefits obtained from telemedicine can be maximized. The results of this study indicate that people's preferences for the use of telemedicine are very diverse, which people give a positive response to the use of telemedicine as a form of health service, as proved by the number of people who will continue to use it in the future. The community also uses telemedicine as a solution to the problems of conventional health services, such as the high cost of services and the service process which is considered to be complicated and take a long time. However, the use of telemedicine is still facing obstacles, one of which is the quality of the application which is considered to be still not good. The use of telemedicine can be a solution to the problems of conventional health services, because telemedicine cannot remove the existing health care system, but is complementary.